Diminishing marginal utility and the teaching of economics: A note - Tamara Todorova (ZBW – Leibniz Information Centre for Economics, 2020)
This paper discusses how utility can be taught in undergraduate courses in microeconomics so that to illustrate total and marginal utility, the law of diminishing marginal utility, and consumer rationality. Diminishing marginal utility is essential in describing rational consumer behavior, overconsumption, and oversaturation to students of economics. We demonstrate a quadratic and a logarithmic total utility with the subsequent forms and shapes of marginal utility. From what it seems there is no contradiction between diminishing marginal utility in the univariate context of consuming one good and the indifference curve as the multivariate case of two goods consumed.
Keywords: B13; B41; D01; D11; 330; total utility; marginal utility; indifference curve